2012
DOI: 10.1021/am201763z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tribochemistry in Nanowear of Single-Crystalline Silicon

Abstract: The effects of counter-surface chemistry, relative humidity, and applied normal load on nanowear of single-crystalline silicon were studied with atomic force microscopy. In the absence of humidity, the silicon surface can resist mechanical wear as long as the contact pressure is lower than the hardness of silicon regardless of the counter-surface chemistry (diamond or SiO(2)) and ambient gas type (vacuum, N(2), O(2), air). In these conditions, the sliding contact region is protruded forming a hillock. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 48 publications
3
138
0
Order By: Relevance
“…In atomic force microscopy (AFM) experiments, the amorphous SiO 2 was shown to be worn with a SiO 2 tip under a low load, while a diamond tip, which is chemically inert yet harder than the SiO 2 , was unable to wear the Si wafer coated with native oxide under a similar load [118,119]. These results suggested that the chemistry of the SiO 2 surfaces contributes to the wear of the material at loads lower than the hardness value causing mechanical deformation of the material.…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 99%
“…In atomic force microscopy (AFM) experiments, the amorphous SiO 2 was shown to be worn with a SiO 2 tip under a low load, while a diamond tip, which is chemically inert yet harder than the SiO 2 , was unable to wear the Si wafer coated with native oxide under a similar load [118,119]. These results suggested that the chemistry of the SiO 2 surfaces contributes to the wear of the material at loads lower than the hardness value causing mechanical deformation of the material.…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 99%
“…The hydrophobization of the contact area on the SiO 2 tip and the silicon surface would reduce both the friction force and the wear rate, as shown in Fig. 11(c) [35,36].…”
Section: Friction-induced Reduction Of Adhesion During the Running-inmentioning
confidence: 99%
“…For example, the nanowear results of silicon surfaces could vary significantly when rubbing against different countersurfaces [14][15][16]. A deep wear of silicon in humid environments occurred only when the counter-surface was SiO 2 , while a hillock formation on the silicon substrate was observed when the counter-surface was diamond [14].…”
Section: Introductionmentioning
confidence: 99%